2016
DOI: 10.2503/hortj.mi-ir05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism Regulating Floral Architecture in Monocotyledonous Ornamental Plants

Abstract: Molecular and genetic analyses of flower development have been conducted primarily in dicot model plants such as Arabidopsis thaliana and Antirrhinum majus. The obtained data are the basis for the ABC model, which was extended to the ABCE model of floral development. This model has been validated in many dicot species using genetic transformation studies and mutant analyses. Many dicot flowers have two distinctive perianth whorls, which include greenish sepals and showy petals. By contrast, the monocot lily fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 102 publications
1
10
0
Order By: Relevance
“…the petaloid sepals (Singh et al, 2014). In the flowers of monocot such as Zingiberales, Commelinales, Alismatales, and Liliales, expanded expression of class B genes into the first floral whorl was correlated with the formation of petaloid organs (Kanno et al, 2007;Hsu et al, 2015;Kanno, 2015;. These results suggested that altering expression pattern of PI orthologous genes caused the transformation from sepal to petaloid organ in flowers.…”
Section: Discussionmentioning
confidence: 94%
“…the petaloid sepals (Singh et al, 2014). In the flowers of monocot such as Zingiberales, Commelinales, Alismatales, and Liliales, expanded expression of class B genes into the first floral whorl was correlated with the formation of petaloid organs (Kanno et al, 2007;Hsu et al, 2015;Kanno, 2015;. These results suggested that altering expression pattern of PI orthologous genes caused the transformation from sepal to petaloid organ in flowers.…”
Section: Discussionmentioning
confidence: 94%
“…Although preliminary RT-PCR analysis showed MaDEF2 expression in all whorls (referred as an unpublished data in Kanno, 2016;Kanno et al, 2007), this was likely because of an excess of PCR cycles in the RT-PCR. Overall, expression profiles of MaGLOA1 and MaDEF1 were consistent with those of the typical Bclass genes proposed in the modified ABC model (Kanno, 2016;Kanno et al, 2003;van Tunen et al, 1993). Among the remaining genes, MaGLOA2 and MaDEF2 seem to have supplemental or perhaps redundant functions, as the expression levels of these genes were low.…”
Section: Madef1mentioning
confidence: 99%
“…Genetic analysis of floral homeotic mutants of Arabidopsis thaliana and Antirrhinum majus has led to the classical ABC model (Coen and Meyerowitz, 1991;Weigel and Meyerowitz, 1994). This model explains the dicot floral structure comprising four floral organs, sepals, petals, ABC model to the ABCE model (Honma and Goto, 2001;Kanno, 2016;Pelaz et al, 2000Pelaz et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers exhibit a wide variety of shapes and colors, and sometimes have abnormal phenotypes ( Meyer, 1966 ), including phyllody (replacement of floral organs by leaf-like structures) and double flowers (flowers with extra petals or petal-like structures). Plants with such abnormal flower phenotypes have often been used as commercial cultivars ( Kanno, 2016 ) and genetic resources to study molecular mechanisms of floral development ( Meyerowitz et al , 1989 ; Wellmer et al , 2014 ). In model eudicots such as Arabidopsis thaliana , the identity of floral organs is regulated by floral homeotic genes divided into ABCE-classes based on function (the ABCE-model): A- and E-class genes specify sepal identity; A-, B-, and E-class genes petal identity; B-, C-, and E-class genes stamen identity; and C- and E-class genes carpel identity ( Krizek and Fletcher, 2005 ; Soltis et al , 2007 ; Rijpkema et al , 2010 ).…”
Section: Introductionmentioning
confidence: 99%